A high energy density Li-rich positive-electrode material with superior performances via a dual chelating agent co-precipitation route1. Issue 18 (14th May 2015) - Hou, Peiyu; Xu, Long; Song, Jishun; Song, Dawei; Shi, Xixi; Wang, Xiaoqing; Zhang, Lianqi
<x xml:space="preserve">Abstract</x> A new Li-rich positive-electrode material is successfully achieved via a dual chelating agent co-precipitation route, which delivers a high volumetric energy density of over 2100 W h L−1, superior cycle life and stable high median-voltage.